Longitudinal T cell-derived IFN-γ/IL-17 balances do not correlate with the disease course in two mouse models of experimental autoimmune encephalomyelitis - Kuerten, Stefanie; Wunsch, Marie; Lehmann, Paul V. (Journal of Immunological Methods, 2013)
The concept of TH17 stemness is attracting increasing attention in the field of tumor immunology. The expression of stem cell-like properties and the promotion of long-term immunity by TH17 cells are also of outmost relevance for autoimmunity. Studying two mouse models of multiple sclerosis (MS), we show that CNS antigen-specific TH17 cells occur in high frequencies in the individual mice. However, there was no preferential shift towards a TH17 response over time. These data suggest that there is no evidence for a differential apoptosis rate in TH1 versus TH17 cells in EAE. Apparently the selective enrichment of TH17 cells that can occur under certain conditions such as cancer does not result from an intrinsic property of TH17 cells, but rather from selective pressure present in the microenvironment. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2022-08-05
Keywords: EAE; MS; Stemness; T; T